CaCu3Ti4O12 thin films with non-linear resistivity deposited by RF-sputtering - Foschini, C. R. [UNESP]; Tararam, R. [UNESP]; Simões, A. Z. [UNESP]; Cilense, M. [UNESP]; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier, 2013)
Calcium copper titanate, CaCu3Ti4O12, CCTO, thin films with polycrystalline nature have been deposited by RF sputtering on Pt/Ti/SiO2/Si (100) substrates at a room temperature followed by annealing at 600 °C for 2 h in a conventional furnace. The CCTO thin film present a cubic structure with lattice parameter a = 7.379 ±0.001 Å free of secondary phases. The observed electrical features of CCTO thin films are highly dependent on the [CaO12], [CaO 4], [CuO11], [CuO11Vx 0] and [TiO5.VO] clusters. The CCTO film capacitor showed a dielectric loss of 0.40 and a dielectric permittivity of 70 at 1 kHz. The J-V behavior is completely symmetrical, regardless of whether the conduction is limited by interfacial barriers or by bulk-like mechanisms. © 2013 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; Electron microscopy; Thin films; X-ray diffraction; Calcium copper titanates; Conventional furnace; Cubic structure; Dielectric permittivities; Interfacial barriers; Polycrystalline; Room temperature; Secondary phasis; Dielectric losses; Permittivity; Synthesis (chemical); X ray diffraction